2016
DOI: 10.1080/17533015.2016.1251475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact on audiences of Inside Out of Mind, research-based theatre for dementia carers

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Research-based Theater (RbT) is shaped by both the form of theater, as an embodied, gestural, spatial, imaginative multi-dimensional art form (that is both process/inquiry-oriented and a form of cultural production), and the traditions of research surrounding knowledge production, specifically qualitative research (such as research questions, methodological design, and dissemination plans). Aligned with other interdisciplinary forms of arts-based research, RbT has been taken up by researchers and artists across disciplines to engage broader publics in research processes and findings, for example, from nursing, medical sociology, education, obstetrics, public health, rehabilitation sciences, among others, in addition to theater and performance studies (e.g., please see Belliveau et al, 2020; Belliveau & Lea, 2016; Bird & Donelan, 2020; Eakin & Endicott, 2006; Gallagher & Kushnir, 2020; Goldstein, 2012; Gray et al, 2011; Harris & Sinclair, 2014; Jonas-Simpson et al, 2012; Kazubowski-Houston, 2010; Kontos et al, 2012; Mitchell et al, 2006; Nisker et al, 2006; Schneider, 2017; Schott et al, 2016). However, beyond being interdisciplinary, RbT is also often taken up across paradigms.…”
mentioning
confidence: 99%
“…Research-based Theater (RbT) is shaped by both the form of theater, as an embodied, gestural, spatial, imaginative multi-dimensional art form (that is both process/inquiry-oriented and a form of cultural production), and the traditions of research surrounding knowledge production, specifically qualitative research (such as research questions, methodological design, and dissemination plans). Aligned with other interdisciplinary forms of arts-based research, RbT has been taken up by researchers and artists across disciplines to engage broader publics in research processes and findings, for example, from nursing, medical sociology, education, obstetrics, public health, rehabilitation sciences, among others, in addition to theater and performance studies (e.g., please see Belliveau et al, 2020; Belliveau & Lea, 2016; Bird & Donelan, 2020; Eakin & Endicott, 2006; Gallagher & Kushnir, 2020; Goldstein, 2012; Gray et al, 2011; Harris & Sinclair, 2014; Jonas-Simpson et al, 2012; Kazubowski-Houston, 2010; Kontos et al, 2012; Mitchell et al, 2006; Nisker et al, 2006; Schneider, 2017; Schott et al, 2016). However, beyond being interdisciplinary, RbT is also often taken up across paradigms.…”
mentioning
confidence: 99%
“…Unload programme on audience members and concluded that the use of theatre was successful medium educating and engaging the public in issues experienced by veterans. The effectiveness of this type of storytelling is also found in other, wider, theatre programmes through effective, transformative learning which raised social consciousness and enabled reflection (Madsen, 2018;Schneider, 2017).…”
Section: 'The Elation Was Unbelievable Because Everybody Stood Up And...mentioning
confidence: 95%
“…When creative and innovative methods are used with care staff, family members and allies of people with dementia, they can also be transformative, interrupting routine ways of thinking and inspiring aspects of the caring imagination (Kontos et al, 2020; Kontos et al, 2010). For example research-based theatre on dementia has been found to heighten awareness of key issues for someone with dementia (Schneider, 2017), and when done in the context of residential aged care, increased motivation for staff to use person centred care approaches (Kontos et al, 2010; Kontos & Naglie, 2007b).…”
Section: Methods For Caring Imaginationmentioning
confidence: 99%